1995
DOI: 10.1093/nar/23.13.2371
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the path of the nascent peptide chain through the 23S in the 50S ribosomal subunit

Abstract: Peptides of different lengths encoded by suitable mRNA fragments were biosynthesized in situ on Escherichia coli ribosomes. The peptides carried a diazirine derivative bound to their N-terminal methionine residue, which was photoactivated whilst the peptides were still attached to the ribosome. Subsequently, the sites of photo-cross-linking to 23S RNA were analyzed by our standard procedures. The N-termini of peptides of increasing length became progressively cross-linked to nucleotide 750 (peptides of 6, 9 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 42 publications
5
37
0
Order By: Relevance
“…This apparent The PT center. Interacts with tip of A-and P-site tRNA 39-ends Yusupov et al, 2001;Bashan et al, 2003a) and the rotating CCA; suggested to anchor the rotating moiety (Agmon et al, 2003;Bashan et al, 2003a) A2602 H93 99 PT center; interacts with A-and P-site tRNA 39-ends Yusupov et al, 2001;Bashan et al, 2003a) and the rotating CCA, in the vicinity of the connection to the tRNA acceptor stems; suggested to anchor the rotating moiety, assisting passage of the tRNA 39-end from the A-to the P-site (Agmon et al, 2003;Bashan et al, 2003a) U2609 C loop, H73-93 96 The tunnel's upper part; cross-links to the C terminus of the elongating peptide (Stade et al, 1995) a Phylogenetic conservation across three phylogenetic domains and two organelles. Sample consisting of 930 species (Cannone et al, 2002).…”
Section: Symmetry Breaking In the Network Of A-to P-region Contactsmentioning
confidence: 99%
“…This apparent The PT center. Interacts with tip of A-and P-site tRNA 39-ends Yusupov et al, 2001;Bashan et al, 2003a) and the rotating CCA; suggested to anchor the rotating moiety (Agmon et al, 2003;Bashan et al, 2003a) A2602 H93 99 PT center; interacts with A-and P-site tRNA 39-ends Yusupov et al, 2001;Bashan et al, 2003a) and the rotating CCA, in the vicinity of the connection to the tRNA acceptor stems; suggested to anchor the rotating moiety, assisting passage of the tRNA 39-end from the A-to the P-site (Agmon et al, 2003;Bashan et al, 2003a) U2609 C loop, H73-93 96 The tunnel's upper part; cross-links to the C terminus of the elongating peptide (Stade et al, 1995) a Phylogenetic conservation across three phylogenetic domains and two organelles. Sample consisting of 930 species (Cannone et al, 2002).…”
Section: Symmetry Breaking In the Network Of A-to P-region Contactsmentioning
confidence: 99%
“…4 8, (calculated from a data set of soluble proteins), smaller folding units have sufficient space to adopt conformation in the solvent-filled ribosome channel. Protease protection studies (Blobel and Sebatini, 1970), antibody binding studies (Bernabeu and Lake, 1982), and crosslinking studies (Brimacombe, 1995;Stade et al, 1995) indicate that 30-40 residues of the nascent chain are protected inside the peptide channel. Given that the rise per helical residue is 1.5 8, and the maximal separation of successive main chain C, atoms in extended conformation is 3.3 8, (Robson and Gamier, 1986), residues in a 40-peptide nascent chain could adopt various helical, extended, and coil conformations in the 85 8, long ribosome channel.…”
Section: Folding Of the Nascent Chain In The Peptide Channelmentioning
confidence: 99%
“…The red and yellow colours are intended only to assist visualization, and follow the scheme of Capel et al (1988), as does the numerical labelling of the proteins. In the first column, the intersubunit interface of the small subunit is facing the viewer, which interpretation is supported by the presence of the interface protein S20/L26 (the two designations represent the same protein (Stöffler-Meilicke et al, 1981;Stöffler-Meilicke & Stöffler, 1990;Stade et al, 1995)). The bottom of the small ribosomal subunit is protein-deficient (Capel et al, 1988;Stöffler-Meilicke & Stöffler, 1990) and here is seen to be phosphorus-rich (i.e.…”
Section: Resultsmentioning
confidence: 96%
“…The independent reconstructions seem to have a natural fit when portrayed in this way. The merger was guided using published data on neutron scattering and immunolocalization of proteins and rRNA sequence segments (Stöffler & Wittmann, 1971;Stöffler-Meilicke et al, 1981;Stöffler & Stöffler-Meilicke, 1983;Capel et al, 1988;Walleczek et al, 1988;Stöffler-Meilicke & Stöffler, 1990;Nierhaus, 1991;May et al, 1992;Stade et al, 1995). If we interpret our E. coli ribosome reconstruction as a biologically functional entity, then there is a large central cavity which provides sufficient room to contain two or three molecules of transfer RNA (tRNA) and the necessary ancillary protein factors.…”
Section: Resultsmentioning
confidence: 99%